A cluster of transcripts identifies a transition stage initiating leafy head growth in heading morphotypes of Brassica. (11th March 2022) - Zhang, Kang; Yang, Yinqing; Wu, Jian; Liang, Jianli; Chen, Shumin; Zhang, Lei; Lv, Honghao; Yin, Xiaona; Zhang, Xin; Zhang, Yiyue; Zhang, Lingkui; Zhang, Yangyong; et al.
SUMMARY: Leaf heading is an important and economically valuable horticultural trait in many vegetables. The formation of a leafy head is a specialized leaf morphogenesis characterized by the emergence of the enlarged incurving leaves. However, the transcriptional regulation mechanisms underlying the transition to leaf heading remain unclear. We carried out large‐scale time‐series transcriptome assays covering the major vegetative growth phases of two heading Brassica crops, Chinese cabbage and cabbage, with the non‐heading morphotype Taicai as the control. A regulatory transition stage that initiated the heading process is identified, accompanied by a developmental switch from rosette leaf to heading leaf in Chinese cabbages. This transition did not exist in the non‐heading control. Moreover, we reveal that the heading transition stage is also conserved in the cabbage clade. Chinese cabbage acquired through domestication a leafy head independently from the origins of heading in other cabbages; phylogenetics supports that the ancestor of all cabbages is non‐heading. The launch of the transition stage is closely associated with the ambient temperature. In addition, examination of the biological activities in the transition stage identified the ethylene pathway as particularly active, and we hypothesize that this pathway was targeted for selection for domestication to form the heading trait specifically in Chinese cabbage. In conclusion, our findings on the transcriptome transition that initiated the leaf heading in Chinese cabbage and cabbage provide a new perspective for future studies of leafy head crops. Significance Statement: By profiling the gene expression dynamics during the heading formation in Chinese cabbage and cabbage, as compared with a non‐heading control, we identified a conserved, temperature‐responsive Leaf Heading Transition Stage marked by the transcriptional reprogramming along with the development of folding leaves. We highlight the ethylene pathway, whose genes are activated during the transition in Chinese cabbage, as the unintended target of domestication, which implies the existence of significant variation within the ancestral non‐heading races.